Long-term temperature trends and variability on Spitsbergen: the extended Svalbard Airport temperature series, 1898-2012 - Nordli, Øyvind; Przybylak, Rajmund; Ogilvie, Astrid E.J.; Isaksen, Ketil (Polar research, 2014)
One of the few long instrumental records available for the Arctic is the Svalbard Airport composite series that hitherto began in 1911, with observations made on Spitsbergen, the largest island in the Svalbard Archipelago. This record has now been extended to 1898 with the inclusion of observations made by hunting and scientific expeditions. Temperature has been observed almost continuously in Svalbard since 1898, although at different sites. It has therefore been possible to create one composite series for Svalbard Airport covering the period 1898-2012, and this valuable new record is presented here. The series reveals large temperature variability on Spitsbergen, with the early 20th century warming as one striking feature: an abrupt change from the cold 1910s to the local maxima of the 1930s and 1950s. With the inclusion of the new data it is possible to show that the 1910s were colder than the years at the start of the series. From the 1960s, temperatures have increased, so the present temperature level is significantly higher than at any earlier period in the instrumental history. For the entire period, and for all seasons, there are positive, statistically significant trends. Regarding the annual mean, the total trend is 2.6°C/century, whereas the largest trend is in spring, at 3.9°C/century. In Europe, it is the Svalbard Archipelago that has experienced the greatest temperature increase during the latest three decades. The composite series may be downloaded from the home page of the Norwegian Meteorological Institute and should be used with reference to the present article.